Total flavonoids of Radix Tetrastigma suppress inflammation-related hepatocellular carcinoma cell metastasis - Zhendong Liu; Fangmi Ding; Xingyong Shen (Molecular Genetics and Genomics, 2021)
This study aimed to investigate the effects of the total flavonoids of Radix Tetrastigma (RTF) on inflammation-related hepatocellular carcinoma (HCC) development. Extracted RTF was diluted to different concentrations for subsequent experiments. HCC cells were cotreated with lipopolysaccharide (LPS) and RTF to investigate the effects of RTF on LPS-stimulated HCC cells. A CCK-8 kit was used to measure cell proliferation. Apoptosis was detected with a flow cytometer. Cell migration and invasion were quantified by wound healing and Transwell assays, respectively. The expression of TLR4 and COX-2 and activation of the NF-κB pathway were determined by Western blotting. Treatment with LPS significantly enhanced cell proliferation and decreased the apoptosis rate, while cell migration and invasion were notably upregulated. RTF suppressed the proliferation and invasion induced by LPS stimulation and promoted HCC cell apoptosis. The protein levels of Bax and cleaved caspase-3 were decreased and that of Bcl-2 was increased by LPS in HCC cells, which could be rescued by RTF. RTF significantly inhibited the LPS-induced expression of the proinflammatory mediators IL-6 and IL-8 in HCC cells. Mechanistically, with RTF treatment, the upregulated expression of TLR4 and COX-2 induced by LPS was obviously downregulated. Furthermore, the phosphorylation of NF-κB/p65 was significantly decreased in LPS-stimulated cells after supplementation with RTF. Our study suggests that RTF exerts a significant inhibitory effect on the LPS-induced enhancement of the malignant behaviors of HCC cells via inactivation of TLR4/NF-κB signaling. RTF may be a promising chemotherapeutic agent to limit HCC development and inflammation-mediated metastasis.